Deposition and characterization of silver nano-films by a novel solid liquid interface reaction technique (SLIRT) - Godbole, P. D.; Mitra, A.; Pasricha, R.; Mandale, A. B.; Patil, K. R. (Materials Letters, 2005)
Solid-liquid interface reaction technique (SLIRT) is used to deposit silver film on glass substrate. The solid film of silver nitrate is formed by modified spin coating method. This film is subsequently processed by dipping it in a reducing solution so as to initiate a reaction at the interface and ultimately transform it to totally silver film. In situ transformation of silver nitrate to silver is studied with respect to time spectrophotometrically. The characterization of silver film is done by various physicochemical techniques namely XRD, XPS, ED, TEM and UV visible spectroscopy. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Electron microscopy; Nano-Particles; solid-liquid interface reaction; thin film

Growth of PbS nanopyramidal particulate films for potential applications in quantum-dot photovoltaics and nanoantennas - Hawaldar, Ranjit R.; Mulik, Uttam P.; Patil, K.; Pasricha, R.; Sathaye, S.; Lewis, A.; Amalnerkar, Dinesh P. (Materials Research Bulletin, 2005)
We report a simple interfacial process called the liquid-liquid interface reaction technique (LLIRT) that leads to the formation of nanosized PbS particulate films with hitherto unreported pyramidal morphology. The resultant PbS films were characterized by transmission electron microscopy (TEM) with selected area electron diffraction (SAED), X-ray diffractometery (XRD), atomic force microscopy (AFM), near field scanning optical microscopy (NSOM) and UV-vis spectroscopy. The pyramidal morphology is speculated to originate from the preferred orientation of the 2 2 0 plane of cubic PbS. Our nanopyramidal PbS particulate films display remarkably sharp excitonic peak centered around 656 nm that accounts for a band gap of 1.8 eV suggesting, in turn, their potential application in QD photovoltaics. Interestingly, the feasibility of such nanopyramids to potentially act as nanoantennas (as revealed by the NSOM) is also suggested. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Atomic force microscopy; Chemical synthesis; Electron microscopy; Nanostructures; Optical properties

Synthesis of bismuth oxide nanoparticles by citrate gel method - Anilkumar, Mettu; Pasricha, R.; Ravi, V. (Ceramics International, 2005)
A mixture of bismuth nitrate and citric acid solution is taken in 1: 1 molar ratio and heated on hot water bath. A gel is formed on evaporation of the water, which on decomposition at 400 degrees C produces nanocrystalline Bi2O3 particles. Formation of nanocrystallites of Bi2O3 is confirmed by X-ray diffraction (XRD) study. Transmission electron microscope (TEM) investigations revealed that the average particle size is 50 nm for these powders. (c) 2004 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Electron microscopy; powders : chemical preparation; X-ray methods

Synthesis of bismuth oxide nanoparticles using bismuth nitrate and urea - Jha, Ratnesh Kumar; Pasricha, R.; Ravi, V. (Ceramics International, 2005)
A mixture of bismuth nitrate and urea is taken in 1:5 molar ratio and heated on hot water bath. A precipitate is formed on evaporation of the water which on decomposition at 400 degrees C produces nanocrystalline Bi2O3 particles. Formation of nano crystallites of Bi2O3 is confirmed by X-ray diffraction (XRD) study. Transmission electron microscopy (TEM) investigations revealed for these powders an average particle size of 50 nm. (c) 2004 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: calcination; Electron microscopy; X-ray methods

Synthesis of fine particles of ZnO at 100 degrees C - Dhage, S. R.; Pasricha, R.; Ravi, V. (Materials Letters, 2005)
A simple gel to crystal conversion route has been followed for the preparation of fine ZnO at 80-100 degreesC under refluxing conditions. Freshly prepared zinc hydroxide gel is allowed to crystallize under refluxing and stirring conditions for 4-6 It. Formation of fine crystallites of ZnO is confirmed by X-ray diffraction (XRD) study. Transmission electron microscope (TEM) investigations revealed that the average particle size is 100 nm for these powders. (C) 2004 Elsevier B.V All rights reserved.
Keywords: Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray diffraction

Synthesis of Sr0.5Ba0.5Nb2O6 by urea method - Dhage, S. R.; Pasricha, R.; Ravi, V. (Materials Letters, 2005)
A precipitate was formed when an aqueous solution of SrCl2, BaCl2, NbF5 and urea in stoichiometric ratio (total metal cations to urea ratio is 5) is heated on a water bath.. This precipitate on decomposition at 750 degreesC yielded the nanocrystallites of ternary oxide, Sr0.5Ba0.5Nb2O6 (SBN) as confirmed by X-ray diffraction study (XRD). This is much lower temperature as compared to that prepared by traditional solid state method (1000 degreesC as reported for the formation of SBN ceramics. Transmission electron microscope (TEM) investigations revealed that the average particle size is 100 nm for the calcined powders. The room temperature dielectric constant at 1 kHz is found to be 1050. The ferroelectric hysteresis loop parameters of these samples were also studied. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Electron microscopy; ferroelectricity; Oxides